The Transition in Eastern Europe, 2 : Restructuring. - Blanchard, Olivier (Olivier J.) (National Bureau of Economic Research project report., 1994)
When communism fell in 1989, the question for most Eastern European countries was not whether to go to a market economy, but how to get there. Several years later, the difficult process of privatization and restructuring continues to concern the countries of the region. The Transition in Eastern Europe, Volumes 1 and 2 is an analysis of the experiences of various countries making the transition to market economies and examines the most important challenges still in store. Volume 1, Country Studies, gives an in-depth, country-by-country analysis of various reform experiences, including historic.